Rethinking Film and Race: the representation of black woman in two western films - ‘Django unchained’ (2012) and ‘the help’ (2011) - Karidza, Bridget (Midlands State University, 2020)
The aim of the study was to explore the frames used in the representation of black women in two western films namely ‘The Help’ (2011) and ‘Django Unchained’ (2012). A qualitative research approach was used and data was collected through Questionnaires, Archival research and personal Observations methods. The study was also informed by Framing and Audience Reception theories. The study found out that black women are depicted as slaves and domestic workers working under white man in western films as exemplified by the two cited films. The study recommends that the film producers, writers, directors and actors should be gender sensitive when representing either men or women in films